Evaluating Lipid‐Lowering Drug Targets for Parkinson's Disease Prevention with Mendelian Randomization. Issue 5 (7th September 2020) - Williams, Dylan M.; Bandres‐Ciga, Sara; Heilbron, Karl; Hinds, David; Noyce, Alastair J.; ,; ,
Abstract : Long‐term exposure to lipid‐lowering drugs might affect Parkinson's disease (PD) risk. We conducted Mendelian randomization analyses where genetic variants indexed expected effects of modulating lipid‐lowering drug targets on PD. Statin exposure was not predicted to increase PD risk, although results were not precise enough to support benefits for prevention clearly (odds ratio [OR] = 0.83; 95% confidence interval [CI] = 0.65, 1.07). Other target results were null, except for variants indicating Apolipoprotein‐A5 or Apolipoprotein‐C3 inhibition might confer protection. These findings suggest peripheral lipid variation may not have a prominent role in PD etiology, but some related drug targets could influence PD via alternate pathways. ANN NEUROL 2020;88:1043–1047